Growth Volatility in Paraguay : Sources, Effects, and Options - World Bank (Washington, DC, 2015)
The purpose of the current study is to contribute to a deeper understanding of growth volatility in Paraguay and to provide an input into the discussion on how to better manage it. In particular, the study will ask three questions: i) what are the sources of volatility in Paraguay? ii) How does growth volatility, in particular that arising from the strong dependence on the agricultural sector, impact the rest of the economy? iii) What are optimal policies for managing the types of volatility observed in Paraguay?